Sandy Hook : an American tragedy and the battle for truth - Williamson, Elizabeth (Journalist) (Dutton, an imprint of Penguin Random House LLC, 2022)
"Based on hundreds of hours of research, interviews, and access to exclusive sources and materials, Sandy Hook is Elizabeth Williamson's landmark investigation of the aftermath of a school shooting and the work by a group of Sandy Hook parents to defend themselves and the truth of their children's fate against the frenzied distortions of online deniers and conspiracy theorists"--Dust jacket flap.